KEPRAKTISAN APLIKASI BERBASIS ANDROID BERMUATAN ETHNOMATHEMATICS UNTUK MENGEMBANGKAN KEMAMPUAN SPASIAL - Henry Suryo Bintoro; Sumaji Sumaji; Jayanti Putri Purwaningrum; Savitri Wanabuliandari; Ratri Rahayu; Himmatul Ulya (Universitas Muhammadiyah Semarang, 2023)
Spatial abilities are very important for students to solve everyday problems, especially spatial ones. Materials are required in the form of applications on devices to make them engage for students. Local wisdom needs to be included in the material content to increase interest in learning. The use of an android-based application with ethnomathematics content is a recommended solution for learning geometry to develop spatial abilities. The research objective in this article is to analyze the practicality of android-based applications with ethnomathematics content on students' spatial abilities. The research method refers to research and development (R&D) methods. This article only examines one part of the R&D research, namely the practicality of android-based applications with ethnomathematics content. The data collection technique used was a learning response questionnaire sheet. The analysis technique used includes qualitative analysis for preliminary studies and quantitative analysis of students' and lecturers' responses to the use of android-based applications with ethnomathematics content. The results of the study show that android-based applications with ethnomathematical content are practically used to develop spatial abilities. The three aspects of practicality, namely presentation techniques, convenience, and spatial abilities show a very practical assessment. This means that Android-based applications containing ethnomathematics can be implemented in the learning process to develop spatial abilities.